Irritable bowel syndrome and its associated factors in adolescents - Lara Fillekes; Ari Prayogo; Fatima Safira Alatas; Badriul Hegar (Indonesian Pediatric Society, 2014)
Background Irritable bowel syndrome (IBS) is a commonfunctional gastrointestinal disorder. Increasing prevalences havebeen reported in Asian adolescent populations, however, therehave been few reports on Indonesian adolescents.Objective To investigate the prevalence of IBS and associatedfactors among adolescents in Jakarta.Methods This cross-sectional study included senior high schoolstudents in a district of Jakarta. Students were asked to fillquestionnaires based on the Rome III criteria for IBS. They werethen divided into groups: those with IBS and those without IBS,for the purposes of comparison.Results Out of 232 adolescents (145 females and 87 males) withmean age of 16.06 (SD 0.91) years, 14 (6.0%) had IBS. Elevenout of 14 adolescents with IBS reported upper abdominal painas well as periumbilical/lower abdominal pain. Irritable bowelsyndrome was not associated with socioeconomic status, food anddrink habits, the use of antibiotics, or scolding as a parental formof discipline. However, a significant higher proportion in the useof corporal punishment was found in IBS adolescents comparedto the non-IBS (P=0.034). In addition, stress related to scolding,as a parental form of discipline was more likely to be found in theIBS group than in the non-IBS group (P=0.019).Conclusion The prevalence of IBS among adolescents in Jakartais 6%, which is lower compared to those of other Asian countries.Corporal punishment at home and stress related to scolding athome are found to be associated with IBS.